THE EFFECTIVENESS OF PRE-QUESTIONING TECHNIQUE TO TEACH READING COMPREHENSION OF NARRATIVE TEXT - Utami, Indira Puruhita (ELT Forum: Journal of English Language Teaching, 2017)
This article is based on a study which investigated the tenth grade students’ achievement in reading comprehension of narrative text. The objectives of this study is to find out whether pre-questioning technique is effective or not, and to find out it effects on the students’ reading comprehension of narrative text after being taught by using pre-questioning technique. The research design was a quasi-experimental research with non-equivalent control group design. The data were pre-test and post-test scores. Based on the result, the average score of pre-test for the experimental group was 75.78, and for the control group was 75.89. The average score of post-test for the experimental group was 84.89, and for the control group was 77.81. Based on the statistical analysis, it showed that Sig. (2-tailed) was 0.000, it meant that it was lower than 0.05. Therefore, Ho was refused and Ha was accepted. There was a significant difference of students’ achievement in reading comprehension of narrative text between the students taught by using the pre-questioning technique and by using translation technique. By applying pre-questioning technique, the students are able to predict the content of the text before reading the whole text. Moreover, the students to be more active and think critically in reading, get the gist of the text, improve their reading comprehension, and build their interest and motivation. It could be concluded that Pre-questioning is an effective technique than translation technique to teach reading comprehension of narrative text.